2015
DOI: 10.1021/ar500248g
|View full text |Cite
|
Sign up to set email alerts
|

Generating Free Charges by Carrier Multiplication in Quantum Dots for Highly Efficient Photovoltaics

Abstract: CONSPECTUS: In a conventional photovoltaic device (solar cell or photodiode) photons are absorbed in a bulk semiconductor layer, leading to excitation of an electron from a valence band to a conduction band. Directly after photoexcitation, the hole in the valence band and the electron in the conduction band have excess energy given by the difference between the photon energy and the semiconductor band gap. In a bulk semiconductor, the initially hot charges rapidly lose their excess energy as heat. This heat lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…Semiconductor quantum dots (QDs) are used to study the fundamental photophysics of quantum confined systems, as well as, for numerous applications in photovoltaics, solid state lighting, biomedical imaging, and biosensing (Dennis et al, 2012b ; Chuang et al, 2014 ; Lan et al, 2014 ; Ten Cate et al, 2015 ; Kagan et al, 2016 ; Hong et al, 2017 ; Chandran et al, 2018 ; Kong L. et al, 2018 ; McHugh et al, 2018 ). Quantum confinement is easily observed in simple, single semiconductor nanocrystals (NCs): smaller cores are more quantum confined, resulting in an increase in the energy gap between the conduction and valence bands as observed through higher energy (bluer) photon emission following photoexcitation.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor quantum dots (QDs) are used to study the fundamental photophysics of quantum confined systems, as well as, for numerous applications in photovoltaics, solid state lighting, biomedical imaging, and biosensing (Dennis et al, 2012b ; Chuang et al, 2014 ; Lan et al, 2014 ; Ten Cate et al, 2015 ; Kagan et al, 2016 ; Hong et al, 2017 ; Chandran et al, 2018 ; Kong L. et al, 2018 ; McHugh et al, 2018 ). Quantum confinement is easily observed in simple, single semiconductor nanocrystals (NCs): smaller cores are more quantum confined, resulting in an increase in the energy gap between the conduction and valence bands as observed through higher energy (bluer) photon emission following photoexcitation.…”
Section: Introductionmentioning
confidence: 99%
“…1 PbSe QDs receive much attention due to their exceptionally strong quantum confinement properties, and in particular because of the occurrence of carrier multiplication (CM). 26 CM is a process in which one sufficiently energetic photon excites two or more electrons across the band gap. In this way the power conversion efficiency of a solar cell can be enhanced above the Shockley–Queisser limit.…”
mentioning
confidence: 99%
“…While the conducted studies have indicated a significant promise of engineered nanostructures for obtaining enhanced CM, there are still a number of questions and challenges that need to be addressed to fully realize the potential of CM in practical devices. For example, the majority of quantitative insights into CM has been derived from optical spectroscopic studies of solutions of isolated QDs 29 30 31 , while practical devices use films of electronically coupled particles 20 22 32 33 34 35 . The available studies of QD films, however, do not provide a conclusive answer to the question on the effect of electronic coupling on multiexciton yields.…”
mentioning
confidence: 99%